UJI EFEKTIVITAS BEBERAPA JENIS TANAMAN SEBAGAI PESTISIDA NABATI TERHADAP HAMA GUDANG Callosobrunchus sp - Yustina Maria Silvia Wonga Puu; Adrianus A Janggo (Agriculture Faculty of Flores University, 2013)
This research aimed to determine the effectiveness of pesticide plant leaves to the growth of warehouse pest (Callosobrunchus sp)and plant extracts that causes the highest mortality of warehouse pests (CallosobrunchusSp). The design used in this study was a Complete Randomized Block Design (CRBD) with the treatments used are PN0 (aquades), PN1 (Leeksextract), PN2 (extracts of Tagetes), PN3 (leaves Lemongrass Extract). Variable observations in this study are the toxins, contact poisons, nerve poison, repellent and antioviposit. The results showed that the extract of leaves of Tagetes, Lemongrass and Scallion effect on the growth of pest warehouse (Callosobrunchus sp) on observations of Toxins, contact poisons, a nerve poison, repellent and antioviposit. Leaves Tagetes extract is the right plant and effective towards mortality of warehouse pest (Callosobruschus Sp) at 80.89% of poisons contact, the nerve at 84,02%, and 85,05% of repellent activity, antioviposit at 97,6%.